Formaldehyde-free adhesive for artificial board and preparation method of formaldehyde-free adhesive
By using raw materials such as 1-butene-2,3,4-tricarboxylic acid, fumaric acid and other raw materials and modified fillers, formaldehyde-free adhesive is formed, which solves the mechanical properties and environmental protection of artificial board adhesives. Inadequately, high strength and high toughness are achieved, while reducing formaldehyde emissions, improving environmental protection and reliability.
Patent Information
- Application Number
- CN202411631912.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Existing artificial board adhesives have shortcomings in terms of mechanical properties, water resistance, heat resistance and cost-effectiveness, and the formaldehyde used in traditional adhesives is harmful to the environment and human health.
The raw materials such as 1-butene-2,3,4-tricarboxylic acid, fumaric acid, acrylate monomers, silane compounds and bisphenol A type epoxy resin are used to process them through specific preparation steps and modified fillers. Form a formaldehyde-free adhesive to improve the cohesion and adhesive properties of the adhesive.
The excellent mechanical properties and peel strength of formaldehyde-free adhesive are achieved, which reduces potential harm to the environment and human health, and improves the environmental protection and reliability of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a formaldehyde-free adhesive for artificial boards and a preparation method thereof. Background Art
[0002] With the development of modern furniture manufacturing and interior decoration industry, wood-based panels are widely used due to their high cost-effectiveness, convenient processing and environmental protection. In the production process of wood-based panels, adhesives are one of the indispensable key materials, which directly affects the strength, durability and environmental performance of wood-based panels. Traditional wood-based panel adhesives mostly use formaldehyde as the main raw material, but formaldehyde release is harmful to the human body and pollutes the environment. Therefore, the development of formaldehyde-free adhesives has become an urgent need in the industry.
[0003] To address this issue, researchers and manufacturers have begun to explore and apply various formaldehyde-free adhesives. These adhesives are usually based on bio-based raw materials, synthetic resins or modified polymers, and are designed to provide bonding performance comparable to formaldehyde-containing adhesives while reducing or eliminating formaldehyde emissions. Despite certain progress, these formaldehyde-free adhesives still face challenges in terms of mechanical properties, water resistance, heat resistance and cost-effectiveness.
[0004] Chinese invention patent CN117025149A discloses a formaldehyde-free adhesive for non-stick steel plates and its preparation method. The formaldehyde-free adhesive in the invention is prepared from the following raw materials in parts by weight: 60-80 parts of bisphenol A epoxy resin, 2-6 parts of antioxidant, 15-25 parts of core-shell nanoparticles, 3-10 parts of diluent, 2-6 parts of defoamer, 6-8 parts of amine curing agent, and 4-7 parts of curing accelerator. The adhesive prepared by the invention uses bisphenol A epoxy resin as the matrix, and by modifying the filler, hyperbranched polymers are grafted on the surface of the rigid organic metal framework to form core-shell nanoparticles, which can not only improve the compatibility of nanoparticles with the matrix and improve the interfacial adhesion, but also improve the brittleness of the matrix, improve the toughness and mechanical properties of the matrix, and in addition, no volatile organic compounds such as formaldehyde are released in the process, which is environmentally friendly. However, the mechanical properties and peel strength of the formaldehyde-free adhesive prepared by the invention need to be improved. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention aims to provide a formaldehyde-free adhesive for artificial boards that is both environmentally friendly and has excellent mechanical properties and a preparation method thereof, so as to reduce the impact on the environment and human health while ensuring the quality of artificial board products.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0007] A method for preparing a formaldehyde-free adhesive for artificial panels is as follows, in parts by weight:
[0008] Step 1, 10-15 parts of 1-butene-2,3,4-tricarboxylic acid, 5-10 parts of fumaric acid, 5-10 parts of acrylic acid ester monomer, 0.1-0.3 parts of emulsifier and 10-15 parts of water are mixed evenly, heated to 60-70° C., 0.3-0.5 parts of initiator are added, and the mixture is treated for 0.5-2 hours to obtain a pretreated product;
[0009] Step 2, adding 2 to 4 parts of silane compound and 1.5 to 2 parts of epoxy resin to the pretreated product prepared in step 1, stirring evenly and heating to 60 to 80° C., adding 0.1 to 0.3 parts of emulsifier, 0.05 to 0.2 parts of sodium acetate and 0.3 to 0.5 parts of initiator, and continuing the treatment for 1 to 2 hours to obtain a post-treated product;
[0010] Step 3: Evenly mix the post-processed product prepared in step 2 with 1 to 3 parts of modified filler to obtain a formaldehyde-free adhesive for artificial panels.
[0011] The acrylic acid ester monomer is at least one of isobutyl acrylate, methyl methacrylate and cyclohexyl acrylate.
[0012] The silane compound is at least one of decamethyltetrasiloxane, trimethyltriphenylcyclotrisiloxane, hexadecylcyclooctasiloxane, hexamethyl-1,5-dihydroxytrisiloxane, and 3-(isomethacryloyloxy)propyltrimethoxysilane.
[0013] The emulsifier is at least one of triglycerol fatty acid ester, sodium dodecylbenzene sulfonate and Tween 80.
[0014] The epoxy resin is bisphenol A type epoxy resin.
[0015] The initiator is azobisisobutyronitrile.
[0016] The preparation method of the modified filler is as follows, in parts by weight:
[0017] S1. Mix 3-5 parts of p-toluenesulfonic acid and 1-3 parts of chopped carbon fibers and add them to 25-35 parts of toluene, heat to 55-65° C. and keep warm for 0.5-2 hours, filter, and obtain pretreated fibers;
[0018] S2, mixing 1-3 parts of the pretreated fiber prepared in step S1, 0.3-0.5 parts of hydroxypropyl deacetylated chitosan and 40-60 parts of water and heating, gradually adding 5-10 parts of benzal malondialdehyde solution during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1-2:8-9; adjusting the pH value to 4-6 with 1-3 mol / L hydrochloric acid, continuously stirring for 1-3 hours, filtering and washing, and finally drying to obtain a reinforcement material;
[0019] S3. Mix and disperse 1 to 3 parts of reinforcing material with 80 to 120 parts of water, add 0.2 to 0.4 parts of isochorismic acid and 5 to 7 parts of 0.4 to 0.6 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 to 8 with 1 to 3 mol / L sodium hydroxide aqueous solution, and then treat at 75 to 85°C for 1 to 3 hours. After filtering, washing and drying, a modified filler is obtained.
[0020] Preferably, the preparation method of the modified filler is as follows, in parts by weight:
[0021] S1. Mix 3-5 parts of p-toluenesulfonic acid and 1-3 parts of chopped carbon fibers and add them to 25-35 parts of toluene, heat to 55-65° C. and keep warm for 0.5-2 hours, filter, and obtain pretreated fibers;
[0022] S2, mixing 1-3 parts of the pretreated fiber prepared in step S1, 0.3-0.5 parts of hydroxypropyl deacetylated chitosan and 40-60 parts of water and heating, gradually adding 5-10 parts of a composite solution during stirring, wherein the composite solution is mixed with benzalmalonaldehyde, 2-hydroxyterephthalaldehyde and anhydrous ethanol in a mass ratio of 0.5-1:0.5-1:8-9; adjusting the pH value to 4-6 with 1-3 mol / L hydrochloric acid, continuing stirring for 1-3 hours, filtering and washing, and finally drying to obtain a reinforcement material;
[0023] S3. Mix and disperse 1 to 3 parts of reinforcing material with 80 to 120 parts of water, add 0.2 to 0.4 parts of isochorismic acid and 5 to 7 parts of 0.4 to 0.6 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 to 8 with 1 to 3 mol / L sodium hydroxide aqueous solution, and then treat at 75 to 85°C for 1 to 3 hours. After filtering, washing and drying, a modified filler is obtained.
[0024] The functions of each substance in the present invention are as follows:
[0025] As one of the main components of the adhesive, 1-butene-2,3,4-tricarboxylic acid provides the main structure of the resin and increases the interaction force between molecules, thereby improving the cohesion and bonding performance of the adhesive.
[0026] Fumaric acid may be used to adjust the acid value of the resin, affecting its crosslinking density and curing speed, thereby affecting the mechanical properties of the adhesive.
[0027] As active components of the adhesive, acrylate monomers participate in the polymerization reaction and increase the crosslinking degree and stability of the adhesive.
[0028] Emulsifiers are used to improve the uniformity of the mixture, allowing the components to be evenly dispersed and improving the stability and bonding properties of the adhesive.
[0029] Silane compounds may be used to improve the adhesion of adhesives to wood-based panel substrates and increase the water resistance and weather resistance of adhesives.
[0030] As another main component of the adhesive, bisphenol A epoxy resin provides a high-strength cross-linking network and enhances the mechanical properties and heat resistance of the adhesive.
[0031] The initiator is used to initiate the polymerization reaction, so that the acrylic ester monomers and other components are polymerized to form a three-dimensional network structure.
[0032] The modified filler is prepared by a specific method to enhance the interaction between the filler and the matrix, thereby improving the cohesion and bonding properties of the adhesive.
[0033] In the preparation of modified fillers, p-toluenesulfonic acid may be used to treat chopped carbon fibers to increase their surface activity and improve their compatibility with resins.
[0034] Hydroxypropyl chitosan may be used to provide additional hydroxyl groups in the preparation of modified fillers to enhance the cross-linked network of fillers.
[0035] In the preparation of modified fillers, benzalmalonaldehyde is used to strengthen the cross-linking network of fillers and improve the performance of adhesives.
[0036] In the preparation of modified fillers, isochorismic acid reacts with cobalt nitrate to generate cobalt isochorismate, which strengthens the internal structure of the filler and improves the overall strength and toughness of the composite material.
[0037] Cobalt nitrate reacts with isochorismic acid to strengthen the cross-linked network of the modified filler.
[0038] Sodium hydroxide is used to adjust the pH value, optimize the reaction conditions, and improve the stability and performance of the adhesive.
[0039] The combination and interaction of these substances enable the formaldehyde-free adhesive of the present invention to have good mechanical properties and peel strength while maintaining environmental protection characteristics.
[0040] Compared with the prior art, it has the following beneficial effects:
[0041] 1) The formaldehyde-free adhesive for artificial panels provided by the present invention does not use volatile organic compounds such as formaldehyde during the preparation process, thereby reducing potential harm to the environment and human health and improving the environmental friendliness of the product.
[0042] 2) Through a specific raw material ratio and preparation method, the adhesive of the present invention exhibits excellent mechanical properties, including high tensile strength and elongation at break, as well as good peel strength, which makes the adhesive more reliable and durable in the application of artificial boards.
[0043] 3) The present invention enhances the interaction between the filler and the matrix by introducing the modified filler, improves the cohesive force and bonding performance of the adhesive, and thus provides a stronger bonding effect in the manufacturing process of the artificial board. DETAILED DESCRIPTION
[0044] Main sources of substances:
[0045] Chopped carbon fiber, tensile strength: 3530MPA, fiber diameter: 7um, length: 6mm, Jusheng Carbon Fiber (Guangdong) Co., Ltd.
[0046] Hydroxypropyl chitosan: Product number: PA11877, AR substitution degree ≥80.0%, Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0047] Benzalmalonaldehyde: CAS number: 82700-43-4.
[0048] Isochorismic acid: CAS number: 22642-82-6.
[0049] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0050] The design idea of the present invention is to provide an environmentally friendly and excellent formaldehyde-free adhesive for artificial panels and a preparation method thereof, by carefully selecting and combining various raw materials, including 1-butene-2,3,4-tricarboxylic acid, fumaric acid, acrylic ester monomers, silane compounds, bisphenol A epoxy resins, and specific emulsifiers and initiators, and through a series of refined preparation steps, including pretreatment, post-treatment, and preparation of modified fillers, to ensure that the final product is not only free of formaldehyde release, but also has excellent mechanical properties and peel strength. In addition, by introducing specific modified fillers, the interaction between the filler and the matrix is enhanced, and the cohesion and bonding performance of the adhesive are improved, thereby realizing an adhesive that is both environmentally friendly and high-performance.
[0051] Example 1
[0052] A method for preparing a formaldehyde-free adhesive for artificial panels is as follows, in parts by weight:
[0053] Step 1, 12 kg of 1-butene-2,3,4-tricarboxylic acid, 8 kg of fumaric acid, 8 kg of methyl methacrylate, 0.2 kg of Tween 80 and 12 kg of water were mixed evenly, heated to 65° C., 0.4 kg of azobisisobutyronitrile was added, and the mixture was treated for 1 hour to obtain a pretreated product;
[0054] Step 2, add 3kg 3-(isobutyleneoxy)propyltrimethoxysilane and 1.8kg bisphenol A epoxy resin to the pretreated product prepared in step 1, stir evenly and heat to 70°C, add 0.2kg Tween 80, 0.1kg sodium acetate and 0.4kg azobisisobutyronitrile, continue to treat for 1.5 hours, and obtain a post-treated product;
[0055] Step 3: Evenly mix the post-processed product prepared in step 2 with 2 kg of modified filler to obtain a formaldehyde-free adhesive for artificial panels.
[0056] The preparation method of the modified filler is as follows:
[0057] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0058] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of benzal malondialdehyde solution is gradually added during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0059] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0060] Example 2
[0061] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0062] The preparation method of the modified filler is as follows:
[0063] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0064] S2, mixing 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water and heating them, gradually adding 8 kg of 2-hydroxyterephthalaldehyde solution during stirring, wherein the 2-hydroxyterephthalaldehyde solution is prepared by mixing 2-hydroxyterephthalaldehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; adjusting the pH value to 5 with 2 mol / L hydrochloric acid, continuing stirring for 2 hours, filtering and washing, and finally drying to obtain a reinforcement material;
[0065] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0066] Example 3
[0067] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0068] The preparation method of the modified filler is as follows:
[0069] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0070] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of 4-methoxycinnamaldehyde solution is gradually added during stirring, wherein the 4-methoxycinnamaldehyde solution is prepared by mixing 4-methoxycinnamaldehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0071] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0072] Example 4
[0073] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0074] The preparation method of the modified filler is as follows:
[0075] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0076] S2, mixing 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water and heating them, gradually adding 8 kg of 3,4-dihydroxycinnamaldehyde solution during stirring, wherein the 3,4-dihydroxycinnamaldehyde solution is prepared by mixing 3,4-dihydroxycinnamaldehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; adjusting the pH value to 5 with 2 mol / L hydrochloric acid, continuing stirring for 2 hours, filtering and washing, and finally drying to obtain a reinforcement material;
[0077] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0078] Example 5
[0079] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0080] The preparation method of the modified filler is as follows:
[0081] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0082] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of benzal malondialdehyde solution is gradually added during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0083] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of 2,5-dimethyl-2,4-hexadienedicarboxylic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0084] Example 6
[0085] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0086] The preparation method of the modified filler is as follows:
[0087] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0088] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of benzal malondialdehyde solution is gradually added during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0089] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of cis-dienedioic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0090] Example 7
[0091] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0092] The preparation method of the modified filler is as follows:
[0093] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0094] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water were mixed and heated, and 8 kg of a composite solution was gradually added during the stirring process, wherein the composite solution was mixed with benzalmalonaldehyde, 2-hydroxyterephthalaldehyde and anhydrous ethanol in a mass ratio of 0.75:0.75:8.5; 2 mol / L hydrochloric acid was used to adjust the pH value to 5, and the mixture was continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0095] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0096] Comparative Example 1
[0097] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0098] The preparation method of the modified filler is as follows:
[0099] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0100] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of 3-(4-hydroxyphenyl) acrolein solution is gradually added during stirring, wherein the 3-(4-hydroxyphenyl) acrolein solution is prepared by mixing 3-(4-hydroxyphenyl) acrolein and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0101] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of isochorismic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 8 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0102] Comparative Example 2
[0103] The method for preparing a formaldehyde-free adhesive for artificial panels is basically the same as that in Example 1, the only difference being that the method for preparing the modified filler is different.
[0104] The preparation method of the modified filler is as follows:
[0105] S1. 4 kg of p-toluenesulfonic acid and 2 kg of chopped carbon fibers were mixed and added into 30 kg of toluene, and the mixture was heated to 60° C. and kept for 1 hour, and filtered to obtain pretreated fibers;
[0106] S2, 2 kg of the pretreated fiber prepared in step S1, 0.4 kg of hydroxypropyl deacetylated chitosan and 50 kg of water are mixed and heated, and 8 kg of benzal malondialdehyde solution is gradually added during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1.5:8.5; the pH value is adjusted to 5 with 2 mol / L hydrochloric acid, and the mixture is continuously stirred for 2 hours, filtered and washed, and finally dried to obtain a reinforcement material;
[0107] S3. Mix and disperse 2 kg of reinforcing material with 100 kg of water, add 0.3 kg of sorbic acid and 6 kg of 0.5 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 with 2 mol / L sodium hydroxide aqueous solution, and then treat at 80 ° C for 2 hours. After filtering, washing and drying, a modified filler is obtained.
[0108] Comparative Example 3
[0109] A method for preparing a formaldehyde-free adhesive for artificial panels is as follows, in parts by weight:
[0110] Step 1, 12 kg of 1-butene-2,3,4-tricarboxylic acid, 8 kg of fumaric acid, 8 kg of methyl methacrylate, 0.2 kg of Tween 80 and 12 kg of water were mixed evenly, heated to 65° C., 0.4 kg of azobisisobutyronitrile was added, and the mixture was treated for 1 hour to obtain a pretreated product;
[0111] Step 2, add 3kg 3-(isobutyleneoxy)propyltrimethoxysilane and 1.8kg bisphenol A epoxy resin to the pretreated product prepared in step 1, stir evenly and heat to 70°C, add 0.2kg Tween 80, 0.1kg sodium acetate and 0.4kg azobisisobutyronitrile, continue to treat for 1.5 hours, and obtain a post-treated product;
[0112] Step 3: Evenly mix the post-processed product prepared in step 2 with 2 kg of chopped carbon fibers to obtain a formaldehyde-free adhesive for artificial panels.
[0113] Test Example 1
[0114] Mechanical properties test
[0115] The mechanical properties were measured according to GB / T 2567-2021 "Test Method for Properties of Resin Castings". The artificial boards prepared in the embodiments of the present invention and the comparative examples were first cured with a formaldehyde-free adhesive at 170°C for 3 hours and then at 200°C for 1 hour. The tensile strength and elongation at break were recorded. The test results are shown in Table 1.
[0116] Table 1
[0117] Experimental protocol Tensile strength(MPa) Elongation at break (%) Example 1 29.53 89.46 Example 2 28.46 87.82 Example 3 26.41 82.65 Example 4 27.87 84.70 Example 5 28.56 84.82 Example 6 27.09 83.68 Example 7 30.25 90.67 Comparative Example 1 27.40 83.06 Comparative Example 2 26.79 82.74 Comparative Example 3 24.72 76.93
[0118] Test Example 2
[0119] Peel strength test
[0120] According to GB / T 532-2008 "Determination of the bond strength between vulcanized rubber or thermoplastic rubber and fabric", the test was carried out by evenly coating the surface of the polished artificial board with a formaldehyde-free adhesive, activating it at 80°C for 3 minutes and then bonding it. The sample size was 100mm×25mm, and the test was carried out on a universal testing machine after pressurization for 15s. The peeling angle was 180° and the tensile rate was 50mm / min.
[0121] The test results are shown in Table 2.
[0122] Table 2
[0123] Experimental protocol Peel strength (KN / m) Example 1 15.7 Example 2 15.4 Example 3 14.3 Example 4 15.1 Example 5 15.3 Example 6 15.1 Example 7 16.0 Comparative Example 1 15.0 Comparative Example 2 14.9 Comparative Example 3 13.6
[0124] It can be seen from the data in Tables 1-2 that the mechanical properties and peel strength of the formaldehyde-free adhesive for artificial panels prepared in Example 1 are better than those in Examples 2-6 and Comparative Examples 1-3.
[0125] The superior performance of benzylidene malondialdehyde in Example 1 can be attributed to its unique molecular structure and reaction characteristics compared to other aldehyde compounds. Benzaldemal contains carbon-carbon double bonds and two aldehyde groups, which not only enhances the π-π interaction and hydrogen bond formation ability between molecules, but also improves the interaction force between molecules. In addition, the aldehyde group of benzylidene malondialdehyde can react with carboxyl and hydroxyl to form a stable structure, thereby enhancing the crosslinking degree and stability of the material. The introduction of benzylidene malondialdehyde may also enhance the interaction between modified filler and matrix, and improve the cohesive force and bonding performance of adhesive. These factors work together to make benzylidene malondialdehyde show better mechanical properties and peel strength in formaldehyde-free adhesives.
[0126] Isochorismic acid shows better mechanical properties and peel strength in the present invention, which is mainly due to its unique role in the reinforcing material. Isochorismic acid contains carboxyl and hydroxyl functional groups, which can react with cobalt nitrate to promote the in-situ generation of isochorismic acid cobalt on the reinforcing material. This in-situ generated isochorismic acid cobalt not only enhances the internal structure of the reinforcing material, but also improves the overall strength and toughness of the composite material. In contrast, 2,5-dimethyl-2,4-hexadienedicarboxylic acid, cis-hexadienedicarboxylic acid and sorbic acid may not effectively promote the reinforcement of the reinforcing material and the improvement of the performance of the composite material like isochorismic acid due to the insufficient number or reactivity of the functional groups. Therefore, isochorismic acid performs better in improving the mechanical properties and peel strength of formaldehyde-free adhesives for artificial boards, thanks to the efficient reaction of its functional groups with the reinforcing material and the remarkable effect on the reinforcing effect of the reinforcing material.
[0127] Embodiment 7 adopts the mode of compounding benzylidene malondialdehyde and 2-hydroxyterephthalaldehyde, and can achieve better effect than the embodiment using one of the aldehyde compounds alone, which is mainly due to the comprehensive effect of the compounded solution. Benzalkonium dialdehyde has a carbon-carbon double bond and two aldehyde groups, which can provide strong cross-linking ability and reactivity; while 2-hydroxyterephthalaldehyde contains phenolic hydroxyl groups and benzaldehyde groups, which can provide additional hydrogen bond formation sites and cross-linking points. The compounding of these two compounds not only enhances the interaction between molecules, including the formation of π-π interactions, hydrogen bonds and covalent bonds, but also increases the number and types of functional groups available for reaction in the system, thereby improving the cross-linking density and stability of the modified filler. This composite cross-linking structure helps to improve the cohesion and bonding performance of the adhesive, thereby improving the mechanical properties and peel strength of the formaldehyde-free adhesive for artificial boards. Therefore, embodiment 7 achieves complementary advantages of the two compounds by compounding benzylidene malondialdehyde and 2-hydroxyterephthalaldehyde, thereby obtaining better comprehensive performance.
Claims
1. A method for preparing a formaldehyde-free adhesive for artificial panels, characterized in that: The method is as follows, in parts by weight: Step 1, 10-15 parts of 1-butene-2,3,4-tricarboxylic acid, 5-10 parts of fumaric acid, 5-10 parts of acrylic acid ester monomer, 0.1-0.3 parts of emulsifier and 10-15 parts of water are mixed evenly, heated to 60-70° C., 0.3-0.5 parts of initiator are added, and the mixture is treated for 0.5-2 hours to obtain a pretreated product; Step 2, adding 2 to 4 parts of silane compound and 1.5 to 2 parts of epoxy resin to the pretreated product prepared in step 1, stirring evenly and heating to 60 to 80° C., adding 0.1 to 0.3 parts of emulsifier, 0.05 to 0.2 parts of sodium acetate and 0.3 to 0.5 parts of initiator, and continuing the treatment for 1 to 2 hours to obtain a post-treated product; Step 3: Evenly mix the post-processed product prepared in step 2 with 1 to 3 parts of modified filler to obtain a formaldehyde-free adhesive for artificial panels.
2. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, wherein: The acrylic acid ester monomer is at least one of isobutyl acrylate, methyl methacrylate and cyclohexyl acrylate.
3. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, characterized in that: The silane compound is at least one of decamethyltetrasiloxane, trimethyltriphenylcyclotrisiloxane, hexadecylcyclooctasiloxane, hexamethyl-1,5-dihydroxytrisiloxane, and 3-(isomethacryloyloxy)propyltrimethoxysilane.
4. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, wherein: The emulsifier is at least one of triglycerol fatty acid ester, sodium dodecylbenzene sulfonate and Tween 80.
5. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.
6. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.
7. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 1, characterized in that: The preparation method of the modified filler is as follows, in parts by weight: S1. Mix 3-5 parts of p-toluenesulfonic acid and 1-3 parts of chopped carbon fibers and add them to 25-35 parts of toluene, heat to 55-65° C. and keep warm for 0.5-2 hours, filter, and obtain pretreated fibers; S2, mixing 1-3 parts of the pretreated fiber prepared in step S1, 0.3-0.5 parts of hydroxypropyl deacetylated chitosan and 40-60 parts of water and heating, gradually adding 5-10 parts of benzal malondialdehyde solution during stirring, wherein the benzal malondialdehyde solution is prepared by mixing benzal malondialdehyde and anhydrous ethanol in a mass ratio of 1-2:8-9; adjusting the pH value to 4-6 with 1-3 mol / L hydrochloric acid, continuously stirring for 1-3 hours, filtering and washing, and finally drying to obtain a reinforcement material; S3. Mix and disperse 1 to 3 parts of reinforcing material with 80 to 120 parts of water, add 0.2 to 0.4 parts of isochorismic acid and 5 to 7 parts of 0.4 to 0.6 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 to 8 with 1 to 3 mol / L sodium hydroxide aqueous solution, and then treat at 75 to 85°C for 1 to 3 hours. After filtering, washing and drying, a modified filler is obtained.
8. The method for preparing the formaldehyde-free adhesive for artificial panels according to claim 7, characterized in that: The preparation method of the modified filler is as follows, in parts by weight: S1. Mix 3-5 parts of p-toluenesulfonic acid and 1-3 parts of chopped carbon fibers and add them to 25-35 parts of toluene, heat to 55-65° C. and keep warm for 0.5-2 hours, filter, and obtain pretreated fibers; S2, mixing 1-3 parts of the pretreated fiber prepared in step S1, 0.3-0.5 parts of hydroxypropyl deacetylated chitosan and 40-60 parts of water and heating, gradually adding 5-10 parts of a composite solution during stirring, wherein the composite solution is mixed with benzalmalonaldehyde, 2-hydroxyterephthalaldehyde and anhydrous ethanol in a mass ratio of 0.5-1:0.5-1:8-9; adjusting the pH value to 4-6 with 1-3 mol / L hydrochloric acid, continuing stirring for 1-3 hours, filtering and washing, and finally drying to obtain a reinforcement material; S3. Mix and disperse 1 to 3 parts of reinforcing material with 80 to 120 parts of water, add 0.2 to 0.4 parts of isochorismic acid and 5 to 7 parts of 0.4 to 0.6 wt% cobalt nitrate aqueous solution, mix well, adjust the pH value to 7 to 8 with 1 to 3 mol / L sodium hydroxide aqueous solution, and then treat at 75 to 85°C for 1 to 3 hours. After filtering, washing and drying, a modified filler is obtained.
9. A formaldehyde-free adhesive for artificial boards, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Water-based wood paint emulsion and preparation method and application thereof
CN110964400A
Formaldehyde-free adhesive for non-stick steel plate and preparation method of formaldehyde-free adhesive
CN117025149A
Adhesive composition
JP2000169822A